Associação do tamanho do corpo e hábito de ostrácodes em relação à arquitetura de plantas aquáticas. - Matsuda, Juliana Tiemi (2014)
Different physical structures present in the environment provide habitat heterogeneity and complexity, increasing the available resources. In this way, they promote greater diversity and abundance of organisms and also are relevant to the establishment and/or mobility of organisms in aquatic systems, being decisive in the species composition. Macrophytes are important structuring the aquatic environment. More complex plants likely to have lower living spaces and increasing organic matter accumulation in its architecture. Thus, they support smaller bodied organisms and those with reduced mobility, more susceptible to discriminate between different substrates. We aimed to assess the role of structural complexity of aquatic plants on the Ostracoda community composition, so we tested the hypothesis that non-swimmers and small size species have strong positive association to more complex plants. Therefore, we analyzed the ostracods communities, from the Upper Paraná River floodplain, associated with ten species of aquatic macrophytes of different structural complexities measured by fractal dimension. The ostracods species were categorized by habit in swimmer/non-swimmer and by body size, in small, medium and large. The relation between the habit and the size of indicator species of ostracods and fractal dimension of the macrophytes was evidenced by the Threshold Indicator Taxa ANalysis (TITAN). The (dis)similarity among plant species was estimated with a principal coordinate analysis (PCoA). However, most of the ostracods species suggested no association with aquatic macrophytes structure, and there was a small variation among the communities from the different plants. Thus, ostracods communities have wide distribution and overlap among the macrophytes of different structures, evidencing that most species have no preferences for habitat complexity. These results allowed us to affirm that the macrophytes complexity is a major contributing factor in structuring the community composition, but there may be interaction with surrounding environmental characteristics and plant identity, affecting each taxon differently. It can thus be concluded that the relation between habitat complexity and the Ostracoda community composition is complex and not always respond to general predictions.